PROPOSED MARKETING STRATEGY FOR PT DWIPUTRA SABARAYA KANCANA (CASE STUDY : RASAMALA HOUSING CLUSTER) (The Indonesian Journal of Business Administration, 2019)
Housing is one of the property sectors that has attractive prospects. This was caused by the demand for houses which were not solely for living quarters. Houses have unique aspects, the demand has two sides based on two motives, namely consumption motives and investment motives. PT. Dwiputra Sabaraya Kancana as one of the housing developers in the city of Bandung for the upper middle market segment. Based on the data, sales for Rasamala cluster have not reached the predetermined target. Reseach objective to identify internal and external factor of Dwiputra Sabaraya Kancana to create marketing mix strategy. Using PESTEL Analysis, Porter 5 forces, client analysis and competitor analysis, this research utilizes internal analysis to comprehend the environment that impacts company. Furthermore, internal analysis to determine the strengths and weaknesses of the business by using STP analysis and marketing mix, then formulating a SWOT, which will lead the research to know the root cause. The first priority is place strategy because of the location is a strategic, with so many accesses housing can provide convenience for consumers to go to location, so that it can attract consumer interest. Price strategy is done by providing convenience in payment, that is, it can be done by hard cash, cash step by step, and by credit (KPR). Promotion strategy by doing it intensively and effectively at print media and electronic / online media. While the product strategy done with the development of quality products, durable and follow the trend by using good raw materials and labor the expert. Keyword: Marketing Mix Strategy, SWOT, Developer, Real Estate